EVALUASI PROSES KERJA PROYEK PEMBANGUNAN DENGAN PENDEKATAN ALTERNATIF PROJECT EVALUATION AND REVIEW TECHNIQUE: (STUDI EMPIRIS PADA ROYAL SENTRALAND MAKASSAR) - Mu’tasyimah; Nofri, Okta; S. Widad Ahmad (Study of Scientific and Behavioral Management, 2025)
This research aims to find out the most appropriate estimated time to complete a construction project at the Royal Sentraland Makassar housing complex using the PERT method. This research uses quantitative research methods. This research uses primary data, namely from every activity that has been carried out, the dependency relationship of every work carried out and what is the cause of every delay that occurs in every project work item. Based on the results of research conducted using the alternative approach PERT (Project Evaluation and Review Technique) which produces an estimate of the correct time to complete the development project at the Royal Sentraland Makassar housing complex. The results of calculations using PERT can show the amount of time needed, the level of confidence desired in determining the time of each activity, monitoring of activities, especially those on the critical path, can be more concentrated, and in terms of completion time for the initial one it is 142 days and for the proposal (accelerated) is 132 days, so there is a time efficiency of 10 days.